Contos, roteiros e curtas-metragens: uma proposta de ensino para a EJA - Silva, Marcela Cristiane da (2020)
This dissertation is the result of a research centered on the elaboration and application of an interventionist reading proposal and in the critical analysis of short stories, in the production of scripts and short films, aimed at the Public of Youth and Adult Education (EJA). The study has as specific objectives: to read and produce texts following the conventions of different genres, taking into account multisemiosis and the integration of digital technologies in a reflective, meaningful and critical way; reading tales from Brazilian literature, analyzing and discussing the discursive representations and identifications of the characters built on them through linguistic / semiotic resources; to investigate the representations and identifications of themselves constructed by the students and to relate them to the representations and identifications of the characters in the stories, articulating cultures, the read and the lived, to stimulate the students to the protagonism during the performance of the proposed activities. To achieve these objectives, we rely on assumptions of the Critical Discourse Analysis FAIRCLOUGH, 2001, 2003, 2008; CHOULIARAKI; FAIRCLOUGH, 1999; BATISTA JUNIOR; SATO; MELO, 2018; MAGALHÃES; MARTINS; RESENDE, 2017), in studies on discourse genres (BAKHTIN, 2015), on the teaching of Portuguese Language at EJA (FREIRE, 2002, 2005; OLIVEIRA, 2002), on critical literacy (FREIRE, 2005; MENEZES DE SOUZA, 2011; DUBOC, 2015) and multi-tools ((ROJO; MOURA, 2012; SOARES, 2012; KLEIMAN, 2008), about the short story genres (CANDIDO, 1989; COSSON, 2012; CORTÁZAR, 2004; GOTLIB, 1988; VIEIRA, 2009) , about the script genre (COMPARATO, 1983; FIELD, 2001) and about the short film genre (ALCÂNTARA, 2014; ASSIS BRASIL, 2001; MIQUELANTE; MARSON; LANFERDINI, 2018). We developed a qualitative, ethical, collaborative, strengthening and ethnographic (THOMAS, 1993; GEERTZ, 1978; HAMMERSLEY; ATKINSON, 1995; CAMERON ET AL., 1992; GIEVE; MAGALHÃES, 1994; MAGALHÃES; GIEVE, 1998; IVANIC, 1998). The data were generated through questionnaires, oral and written reports, recordings, portfolio production and various texts in line with the conventions s of different genres and through records in a field diary. As a result, we were able to perceive that the work constituted itself as an opportunity for protagonism of the participating students, for reflection on the uses of language and other semiotic ways in reading and writing, for a critical analysis of the representations and identifications built in the tales and articulation of the read with the lived, promoting a greater approximation of the readers of the EJA to the literary text.